IT Security In The Higher Education Institutions - Dave E. Marcial (Jurnal Informatika, 2012)
This paper investigates the level of prioritization and degree of implementation of IT security in higher education institutions (HEIs) in the Philippines. A total of 95 HEIs in the Philippines were evaluated in the study. The study reveals that the level of prioritization of IT security in the Philippines HEIs is high. This signifies that IT security is prioritized and there is need to be done in the next 3 years in these HEIs. The degree of implementation of IT security in the HEIs is moderately implemented indicating that although this component is in the strategic plan of the HEIs, little or no action has been undertaken in this regard. The study further reveals that the level of prioritization of IT security has a significant correlation at 0.01 level of confidence with the degree of implementation of IT security in the HEIs in the Philippines. Keywords : security, privacy, risk, IT in education